2016
DOI: 10.1002/2016ja022433
|View full text |Cite
|
Sign up to set email alerts
|

The very slow solar wind: Properties, origin and variability

Abstract: Solar wind slower than 300 km/s, hereafter termed very slow solar wind (VSSW), is seldom observed at 1 AU. It was, however, commonly measured inside 0.7 AU by the two Helios spacecraft, particularly during solar maximum. Magnetohydrodynamic (MHD) modeling reveals that the disappearance of VSSW at 1 AU is the result of its interaction with faster solar wind. The acceleration and compression of the VSSW contributes to the observed highly variable structure of the slow solar wind at 1 AU. The VSSW usually contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 52 publications
5
43
0
Order By: Relevance
“…We conclude that, for most of their propagation, CDSs are therefore associated with density variations in the background slow solar wind. Recent analysis of Helios observations near 0.3 AU has revealed that the densest solar wind is associated with the heliospheric plasma sheet and propagates with a speed of less than 300 km s −1 in over 8 % of all observations (Sanchez-Diaz et al, 2016). Additionally, SIR/CIRs are rarely well formed at these heights.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that, for most of their propagation, CDSs are therefore associated with density variations in the background slow solar wind. Recent analysis of Helios observations near 0.3 AU has revealed that the densest solar wind is associated with the heliospheric plasma sheet and propagates with a speed of less than 300 km s −1 in over 8 % of all observations (Sanchez-Diaz et al, 2016). Additionally, SIR/CIRs are rarely well formed at these heights.…”
Section: Discussionmentioning
confidence: 99%
“…We note that this velocity is about four times lower than that of the very slow solar wind (e.g., Sanchez-Diaz et al 2016), or the wind of the K-type host star HD 189733b (as derived by Bourrier & Lecavelier des Etangs 2013 from transit observations of its evaporating hot Jupiter companion).…”
Section: Simulations Of Hydrogen Exospheresmentioning
confidence: 93%
“…Dividing this number by the area of that sphere, we derive a proton flux of 1.7 × 10 11 m −2 s −1 due to blobs during the period of study. If we assume that the proton flux of the solar wind at 1 au is 2.5 × 10 12 m −2 s −1 (Wang 2010;Sanchez-Diaz et al 2016), and that 40% to 50% of the solar wind is SSW during solar maximum (Tokumaru et al 2010), we estimate that the proton flux released into the solar wind in the form of blobs would represent around 15% of the bulk of the whole SSW at solar maximum. Based on in situ measurements, Kasper et al (2007) and McGregor (2011) suggest that there are two sources of SSW.…”
Section: Contribution Of Blobs To the Total Mass Flux Of The Slow Solmentioning
confidence: 99%
“…Provided that the total proton flux of the SSW is known from in situ measurements at 1 au (Wang 2010;Sanchez-Diaz et al 2016), the fraction of the SSW mass flux transported by blobs alone may be obtained by exploiting heliospheric imagery to retrieve the sizes, release rate, and spatial distribution of blobs. The tracking of blobs to 1 au, and their identification in situ, is only possible for certain spacecraft configurations.…”
Section: Introductionmentioning
confidence: 99%